2002
DOI: 10.21273/hortsci.37.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Regulators Affect the Development of Both Corms and Cormels in Gladiolus

Abstract: The effects of BA, ethephon, and GA3 on freshly harvested cormels of three cultivars of Gladiolus sp. were studied for 3 years. The treatment with 400 mg·L-1 ethephon significantly reduced the dormancy period by 17.5 days as compared to control, while BA and GA3 were found to be less effective. Among all treatments, ethepon at 400 mg·L-1 was found to be the most effective in altering the days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
10
1
Order By: Relevance
“…Also, in contrast with Napier et al (1986) on Leucospermum pointed out that 200 ppm applied once in late summer increased the number of florets and increased flower stem diameter. Also, In contrast with our results, Ram et al (2002) reported that BA increased corm diameter and weight and cormel number and weight of Gladiolus. BA is a cytokinin known to increase cell division (Hartmann et al, 2001) and favour shoot formation (Leclerc et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…Also, in contrast with Napier et al (1986) on Leucospermum pointed out that 200 ppm applied once in late summer increased the number of florets and increased flower stem diameter. Also, In contrast with our results, Ram et al (2002) reported that BA increased corm diameter and weight and cormel number and weight of Gladiolus. BA is a cytokinin known to increase cell division (Hartmann et al, 2001) and favour shoot formation (Leclerc et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…However, it is not an ABA-specific inhibitor; our results show that fluridone inhibits root elongation, which has also been demonstrated in previous research ( Hooker and Thorpe, 1998 ; Spollen et al, 2000 ). Although GA has proven to be important in seed dormancy, it may play a limited role in corm dormancy ( Ram et al, 2002 ; Finkelstein et al, 2008 ). GA content increases only in the late dormancy-releasing period and fluctuates irregularly during dormancy breaking ( Figure 1B ).…”
Section: Discussionmentioning
confidence: 99%
“…GA content increases only in the late dormancy-releasing period and fluctuates irregularly during dormancy breaking ( Figure 1B ). Previous studies have shown that GA has a limited effect on Gladiolus corm dormancy ( Ram et al, 2002 ). In addition, corm dormancy and seed dormancy share a common physiological characteristic: they are both heavily regulated by ABA ( Ahrazem et al, 2012 ; Finkelstein, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dormancy of gladioli corms can also be shortened with ethylene , by soaking corms in 20 ppm benzyladenine (BA) followed by 100 ppm gibberellic acid (GA) (Tsukamoto, 1979), with ethanol (Hosoki, 1983), with a 4-hour treatment of methyl disulfide (Hosoki & Kubara, 1989) or with 400 mg 1-1 ethephon (Ram et al, 2002). The standard forcing technique is to place the corms in controlled temperature rooting rooms thus manipulating the corms to obtain year-round control of the corm cycle (De Hertogh & Le Nard, 1993).…”
Section: Production Phasementioning
confidence: 99%